The implementation of hub and spokes concept for sustainable transport in UNIC Leisure Company - Ashari, Hasbullah; Othman, Fathiah; Husin, Fatihah; Farhan, Nasriq (2015)
The purpose of this study is to identify the implementation of the hub and spoke concept for sustainable transportation in the UNIC Leisure Company. Sustainable transport should capture attributes of system effectiveness and system impact on economic development, environmental integrity and social quality of life.There are several issues in this study, which are: high operational and transportation cost, low capacity and inefficient time management.In order to carry out the study, qualitative analysis in which enquiry observation technique was conducted for the UNIC Leisure Company services. Based on the findings, this study will propose the hub and spoke concept to the UNIC Leisure Company.This study can assist the company to improve the effectiveness and efficiency in terms of their bus services.Besides that, this study also enriches the case study related to sustainable transport, which will benefits logistics student.